(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The performance improvement of the T-type DVR Multilevel Inverter for Solar PV Integrated with Grid based Constant Current Controller is defined in this paper. The T-type DVR Multilevel Inverter has decreased the number of switches here. The Controller used for the DVR based T-type MLI is Constant Current Controller which is in cooperated to the solar PV Power Generator with integration to the Grid. A 3 Phase PLL is used in Constant Current Controller for utility grid phase angle tracking and this mechanism will react fast enough to the load changes or different states of Grid connection. This result is supplying constant voltage without any phase jump to the load. Results are discussed for load currents for supplying 2mw load and even a load about 30Mw, 2MVAR. By using Matlab/Simulink, the overall framework is planned and modeled.